Potensi Tegakan Pada Hutan Lindung Bekas Pertambangan Tradisional Kabupaten Mandailing Natal (The Potential of Stands in the Former Traditional Mining Preserve Forest Mandailing Natal) - Budi Utomo; Mohammad Basyuni; Mukti Batubara (FORESTA, 2012)
The effects of the damage of preserve forest will cause flooding in the rainy season, droughts during the dry season and disturbing watersheds within and outside the forest area. The purpose of this study was to evaluate the diversity of tree species, regeneration of stands and calculate the potential of forest stands in traditional mining, and preserve areas without mining. The method in this research is line, plot with 100 m length and a width of 20 m. Data analyzed by the Shannon-Winner’s diversity index. The results showed that we obtained 18 plant species of traditional mining and had middle tree diversity. In contrest, preserve forest with out mining, we found 29 plant species with high tree diversity ((H '=3.02). The potential stands of the tree level in the former traditional mining preserve forest was 76.28 m3/ha, and in the preserve forest without mining was 925.53 m3/ha. Traditional mining in the preserve forest significantly influenced the density of vegetation according to the result of the Wilcoxon rank test.Key Words: the potential of stands, traditional mining, protected forests, analysis vegetation, Mandailing Natal Regency.